Relationship of Nursing Behavior with Treatment of Nosocomial Infections in RSUS Delitua in 2018 - Agustina Simamora (Talenta Publisher, 2019)
Most patients who are hospitalized get treatment and treatment from nurses according to their respective complaints. The behavior of nurses in these patients mostly can make an infection because often the action is taken in the form of therapy or not. Infection that often occurs in a hospital is called a nosocomial infection, nosocomial infection is an infection that is obtained during a patient's hospital treatment. Currently nosocomial infection is one of the causes of increased morbidity and mortality in hospitals. The aim of this study is to know in general the relationship between nurses' behavior and nosocomial infection control in Sembiring Delitua Hospital in 2018. This research is descriptive correlational, which identifies the causal relationship between the behavior of nurses and the prevention of nosocomial infections in Sembiring Delitua General Hospital in 2018. Based on the results obtained, the respondents' knowledge and attitudes in Sembiring Delitua General Hospital in 2013 will be able to overcome nosocomial infections. say well according to the results of a good questionnaire and on the respondent's actions both based on the observations of the respondent's actions can be said to be good. Thus the researchers hope that the results of this study can be a motivation in improving service quality in improving services for nosocomial infections for nurses.